HOW COOPERATIVE SOCIETIES AFFECT THE MARKETING PERFORMANCE OF RICE PRODUCERS IN BENUE STATE, NIGERIA - Michael , Orngu Tavershima (Research Journal of Economics and Sustainable Development, 2024)
The study examined the effect of cooperative society on the marketing performance of rice producers in Benue State, Nigeria. Data were collected from 746 rice farmers consisting of 375-member rice farmers and 371 non-member rice farmers selected from 137 randomly selected cooperative societies using multistage sampling technique. The results show that 67.5% of rice farmers who are member of cooperative achieved marketing efficiency value of 13.01 and above while 56.6% of rice farmers who are non-member of cooperative achieved marketing efficiency of the same value. The results also reveal that member rice farmers had mean marketing efficiency of 14.14 while non-member rice farmers had a mean marketing efficiency of 12.98 which was significantly different at 1% level. Furthermore, evidence from the results reveal that cooperative society improved the marketing efficiency of the rice farmers by 8.94%. The study recommended that cooperatives societies in the study area should raise awareness among rice farmers of the short and long-term benefits of being a cooperative member through social media, village and church meetings, sports and games, seminars, school clubs, and conferences; and that there should be a deliberate effort by these cooperatives to provide financial and material support to rice farmers who are their members to serve as catalyst to attract non-member rice farmers and retain the existing member farmers in the area